VALUATION OF COSTS FOR MAINTENANCE AND REPAIR OF TRANSPORT VEHICLES, TAKING INTO ACCOUNT OPERATING CONDITIONS (Transport systems and technologies, 2018)
The legislation of Ukraine does not adjust the mileage between technical services and to determine the total resource of the car. The state of the road greatly affects the reliability and durability of the machine. The purpose of the work is to link the cost of maintenance and repair with the operating conditions of cars. The quality of the road surface is estimated by the degree of evenness, which is obtained from the measurement of movement of the body and wheels. Vertical oscillations of the body of the car leads to a change in the power balance on the wheels of the car. Increased losses in the suspensionof the car affect the load of the internal combustion engine. The speed of wear of the engine cylinders depends on the engine speed and the average of indicator pressure. The article gives an analytical dependence of the relationship between the flatness of theroad and the engine life. The adjustment of the mileage between maintenance and the vehicle resource is proposed to be carried out through a correction factor. In this paper, a formula is derived for calculating this correction factor. The coefficient was calculatedusing the example of Skoda Octavia. The graphs of the vehicle’s resource change are obtained from the road roughness and speed car. For the first time the degree of loading of the car at rationing of the periodicity of maintenance is taken into account. The receivedmathematical model is proposed to be applied at automobile transport enterprises, in order to prolong the level of reliability and durability of the machines due to timely maintenance in difficult operating conditions.
Keywords: vehicle, durability, reliability, service, maintenance work, operating conditions, mathematical modeling.